Puberty of Katingan cow in realation to Cu mineral and the environtment - BN, Utomo; RR, Noor; C, Sumantri; I, Supriatna; ED, Gurnardi (Indonesian Animal Sciences Society, 2013)
The onset of puberty is an important role in order to optimize performance of Katingan cattle reproduction. The onset of puberty can be estimated from to blood progesterone concentration. In this study the onset of puberty was estimetid through analysis of progesterone hormone in various age of individual cattle. Thirty blood samples were obtained from 30 Katingan heifers of 13 months and 15 days to 23 months and 18 days old from Tumbang Lahang (10 samples) and Buntut Bali (20 sampels) to be analyzed for progesterone concentrations using RIA method. The same samples were also analyzed to find out information about Copper (Cu) concentration. The results showed that progesterone concentration varied narrowly from 0.008 to 0.184 ng/ml. The result indicated that the Katingan cattle in 23 months old was still in prepuberty category. Environment factor such as land pH was acid (pH<6), grass quality and climate in term of temperature and humidity relatively high, may an important role to delay the oset of their puberty. One of the environment problem was proved by the most of the same samples than had under adequate value of level of Copper. Â Key Words: Katingan Cattle, Progesterone, Puberty, Cu mineral, Environment